Land Conflict Management as an Effort to Secure Serang Regency Government Assets - Rahmawati Rahmawati; Dyah Lituhayu (Jurnal Administrasi Publik (Public Administration Journal), 2022)
This paper aims to analyze the management of land conflicts that occurred in the assets of the Serang Regency Government as a form of securing their assets. The problem is focused on efforts to solve land disputes or conflicts and the asset security strategies that were carried out. To approach this problem, Fisher's theory of conflict management and Siregar's asset management theory were used. Data were collected through interviews, observation, and literature study and analyzed descriptively qualitatively. This study shows that land asset conflicts occur predominantly between individuals and the Serang Regency Government regarding land grants given for the use of public facilities such as education and health, however without being accompanied by official documents. Settlement of land disputes was carried out through a compromise approach and reaches the court level if no common solution was found. Dispute resolution aims to administratively complete land ownership documents. Physically avoiding illegal land use and legal security related to dispute resolution through the courts to determine the legal ownership of disputed land assets. It can be concluded that Serang Regency Government must fix all land disputes that occur so that the land assets owned can be maximized and do not disturb the socio-political stability in the society.